PERANCANGAN SISTEM INFORMASI PEMINJAMAN AULA PADA KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI SUMATERA SELATAN - Silva Melvina; Muhamad Son Muarie (CV. Denasya Smart Publisher, 2026)
The management of hall borrowing at the Regional Office of the Ministry of Religious Affairs of South Sumatra Province is still carried out manually through written requests and manual records, which often causes problems such as schedule conflicts, delayed information, and inefficient administrative processes. This study aims to design a hall borrowing information system that can manage the submission, scheduling, and approval processes in a structured and transparent manner. This research uses a qualitative approach with data collection techniques through observation, interviews, and literature study. The system development method applied is Rapid Application Development (RAD), focused only on the design stage. The results of this study are system design models including use case diagrams, activity diagrams, class diagrams, and user interface designs. This design is expected to become the basis for future system development to improve efficiency, transparency, and accuracy in the hall borrowing process.